2011
DOI: 10.1007/s11046-011-9463-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Paracoccidioidomycosis in Sheep

Abstract: The objective of this study was to evaluate the prevalence of antibodies against Paracoccidioides brasiliensis in sheep from Guarapuava, Paraná State, Brazil. The seroepidemiological study was carried out in 262 sheep. The samples were analyzed by ELISA and immunodiffusion test using P. brasiliensis gp43 and exoantigen as antigens, respectively. Initially, two sheep were immunized with P. brasiliensis to evaluate whether contact with the fungal cells could induce a humoral immune response against gp43 and exoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Epidemiological studies of PCM in domestic and wild animals have been based mainly on immunological reactions using crude paracoccidioidin and purified gp43 as antigens [5][6][7][8][9][10][11][12][13][14][15][16]32]. Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies of PCM in domestic and wild animals have been based mainly on immunological reactions using crude paracoccidioidin and purified gp43 as antigens [5][6][7][8][9][10][11][12][13][14][15][16]32]. Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil. The present study reinforces that ELISA is a useful method for detection of P. brasiliensis infection in animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbits experimentally infected with P. brasiliensis produced antibodies against gp43, suggesting that this antigen can be useful for epidemiological studies of PCM in this species. Other domestic animals such as dogs, cows, sheep, chickens and goats also showed humoral immune response against gp43 antigen after immunisation with P. brasiliensis cells.…”
Section: Discussionmentioning
confidence: 99%
“…The infection of domestic and wild animals by P. brasiliensis occurs frequently as reported in several epidemiological studies with dogs, horses, cattle, sheep, chickens, goats coati‐mundi, felines, monkeys and armadillos, although natural disease was reported only in two dogs, a cat and a southern two‐toed sloth …”
Section: Introductionmentioning
confidence: 98%